Outcome of a dedicated complex aortic surgery fellowship program - Arzola, Luis H.; Asciutto, Giuseppe; Shehab, Maysam; Wanhainen, Anders; Mani, Kevin (Frontiers in Surgery, 2024)
Introduction: Advancements in endovascular therapy, especially in complex aortic procedures, underscore the need for additional post-certification training. Dedicated post-residency vascular fellowship programs offer exposure to diverse cases, research opportunities, and professional networking. The study aims to describe and present outcomes from the complex aortic fellowship program at the Vascular Surgery Department of the Uppsala University Hospital.Methods: Nine former fellows who completed the aortic fellowship program at the Uppsala University Hospital from 2018 to 2023 were invited to take part in an anonymous 29-question survey through email. Demographic data, information about the existence of local aortic programs as well as on the types of aortic procedures performed were gained. The overall experience and impact of the fellowship were assessed using multiple interval scale questions, with a rating scale (1 excellent to 5 very poor). Finally, we provided the option to the participants to share additional feedback.Conclusions: There is a universal need for additional post-certification training. The current study showed that a balanced clinical and scientific exposure to complex aortic diseases is broadly welcomed among young vascular surgeons. The extension of the fellowship to cover other disciplines dealing with complex aortic procedures can be of value.